2015
DOI: 10.3390/ijms161125967
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Fluxes between Primary Metabolism and Phenolic Pathway in Plant Tissues under Stress

Abstract: Higher plants synthesize an amazing diversity of phenolic secondary metabolites. Phenolics are defined secondary metabolites or natural products because, originally, they were considered not essential for plant growth and development. Plant phenolics, like other natural compounds, provide the plant with specific adaptations to changing environmental conditions and, therefore, they are essential for plant defense mechanisms. Plant defensive traits are costly for plants due to the energy drain from growth toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
168
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(176 citation statements)
references
References 190 publications
(225 reference statements)
5
168
2
1
Order By: Relevance
“…the oxidative pentose pathway), and this, in turn, will result in the shuffling of carbon atoms in Glc molecules. Indeed, abiotic stress was shown to induce the expression of the oxidative pentose phosphate genes (Caretto et al, 2015). The resulting isotopic dilution of the labeled precursor would affect the subsequent calculations, had it not been corrected for.…”
Section: Discussionmentioning
confidence: 99%
“…the oxidative pentose pathway), and this, in turn, will result in the shuffling of carbon atoms in Glc molecules. Indeed, abiotic stress was shown to induce the expression of the oxidative pentose phosphate genes (Caretto et al, 2015). The resulting isotopic dilution of the labeled precursor would affect the subsequent calculations, had it not been corrected for.…”
Section: Discussionmentioning
confidence: 99%
“…They can prevent insect oviposition on the host plant and disturb larval growth (Caretto et al 2015). For example, flavonoids were shown to inhibit feeding, growth, development and oviposition of various insect species (Simmond 2001(Simmond , 2003Lattanzio et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…By applying the bio-based products on the healthy leaf surface, a possible priming effect was identified in the greenhouse experiment as discussed above, which would imply in the reduction in the fitness cost and consecutively absence of negative effect on plant yield 30 . This was not the case in the non-inoculated field trial, where a lower productivity was identified (Fig.…”
Section: Discussionmentioning
confidence: 99%